Ready or Not? A Pilot Study of Graduate Students' and Instructors' Perceptions of the Effectiveness of Online Support Modules for Enhancing Academic Performance - Amanda L. Townley; Lina B. Soares; Regina Rahimi (MDPI AG, 2023)
Since the beginning of the twenty-first century, graduate studies and the adult students pursuing those studies have drastically changed, creating a new landscape of challenges to success for students and faculty alike. Online learning is fast becoming the norm in graduate studies of education rather than the exception, creating barriers in the form of lost community, looser connections between graduate students and faculty, and a shifting focus on student accountability to enter programs with requisite skills far beyond their counterparts of the past. This study explored the use of online support modules to strengthen deficient skills among graduate students in a fully online Education Specialist program. The use of modules to address issues with academic writing, APA style, locating academic literature, synthesizing studies, and other preparation to write literature reviews proved a valuable and time-efficient tool for managing the remedial needs of students at the graduate level. A survey method was applied to collect data from students and faculty, followed by a thematic analysis of the results. Both students and instructors positively received these support modules. Furthermore, perceptions from both groups highlight the need for further exploration of means to provide modern support for an ever-changing adult student body.